Author’s Response: Theory as Agent - O'Brien, Eugene (ABEI Journal, 2002)
Such conceptual unpacking was a motivating factor in the writing of this book, concerned as it is with those almost hoary tropes of Irish identity and the writings of Yeats and Joyce. As Corbett has suggested, these issues have been discussed ad nauseum and yet, it seemed to me, not within a theoretically driven intellectual paradigm which might tease out some of the nuances within them. It was my hope to defamiliarize some of these ‘givens’ in a discourse paralleling that of Brian Friel, who, in Translations, acknowledges the need for constantly renewing our relationship to language and the images of the past embodied in language. Otherwise, as he puts it, ‘we fossilize.’ My own efforts in the field of renewal relate both to language and ideology, using theory as an agent of defossilization in terms of Irishness in general and Irish nationalism in particular.